Utilization of Infrared Thermography in Cattle Production and Its Application Potency in Indonesia - Diana Bansi (Indonesian Center for Animal Research and Development, 2018)
Infrared thermography (IRT) is a non-invasive remote sensing method to detect temperature. Many studies have shown that temperature in several regions of the body could be representative of core body temperature. Body temperature of cattle can be used to evaluate health status, stress, thermal balance, and feed efficiency. The aim of this article is to review utilization of IRT in cattle production system and its potency to be applied in Indonesia. The ability of IRT to detect even the small change of body surface temperature has made this device is very useful in cattle production industry. Infrared thermography has been used as a tool to detect an early detection of inflammation as sign of some diseases such as mastitis, foot and mouth disease. Infrared thermography can also evaluate feed efficiency through detection of heat production produced by metabolism process. Some important constraints of cattle production in Indonesia such as diseases and low feed efficiency may have strong correlation with body temperature change. Therefore, IRT is very potential to be applied in cattle farms in Indonesia.